Physiological stage dependent hematobiochemical and echocardiographic changes in dromedary camels - Sabry Mousa; Mohamed E. Ali; Amin Tahoun; Ahmed Adel El-Sayed; Mohamed Marzok; Adel I. Almubarak; Rasha Y. Fadl Elmola; Zakriya Al Mohamad; Wael M. El-Deeb; Elshymaa A. Abdelnaby; Mahmoud Kandeel; Doaa Ebrahim; et al. (BMC Veterinary Research)
Abstract Background In livestock, identifying physiological and reproductive stages is crucial for informed decisions in nutrition, healthcare, and breeding management. Objective This study aimed to evaluate hematobiochemical and Doppler echocardiographic changes in dromedary camels during three key stages: non pregnant, late pregnancy, and early lactation. Methodology Thirty healthy camels were monitored across three physiological stages. Blood samples were analyzed for complete blood count (CBC) and serum metabolic parameters, including Beta-hydroxy-butyric acid (BHBA) and non-esterified fatty acids (NEFA). Doppler echocardiography assessed cardiac morphology and function. Results Late pregnancy was associated with a significant (P < 0.05) increase in red blood cell (RBC) count, hemoglobin (Hb), and neutrophils, while packed cell volume (PCV), total white blood cell (WBC) count, and monocytes decreased. Serum glucose and cholesterol declined significantly (P < 0.05) in late pregnancy and early lactation, while Beta-hydroxy-butyric acid (BHBA) increased. Late-pregnant camels showed elevated levels of albumin, globulin, potassium (K), and cardiac troponin, but lower total protein (TP). Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were highest in non-pregnant camels. NEFA levels rose significantly in early lactation. Echocardiographic findings revealed increased left ventricular wall thickness and decreased systolic diameter (LVIDs) in early lactation. Heart rate (HR) increased in late pregnancy. No significant changes were observed in pulsed-wave Doppler indices. Conclusions Distinct physiological stages in dromedary camels are associated with significant hematobiochemical alterations and minor echocardiographic changes, offering valuable insights for clinical and reproductive management.